Potential of Thermal Neutrons to Correct Cosmic‐Ray Neutron Soil Moisture Content Measurements for Dynamic Biomass Effects. Issue 8 (22nd August 2022) - Jakobi, J.; Huisman, J. A.; Fuchs, H.; Vereecken, H.; Bogena, H. R.
Abstract: Cosmic‐ray neutron sensors (CRNS) enable noninvasive determination of field‐scale soil moisture content by exploiting the dependence of the intensity of aboveground epithermal neutrons on the hydrogen contained in soil moisture. However, there are other hydrogen pools besides soil moisture (e.g., biomass). Therefore, these hydrogen pools should be considered for accurate soil moisture content measurements, especially when they are changing dynamically (e.g., arable crops, deforestation, and reforestation). In this study, we test four approaches for the correction of biomass effects on soil moisture content measurements with CRNS using experiments with three crops (sugar beet, winter wheat, and maize) based on high‐quality reference soil moisture: (a) site‐specific functions based on in‐situ measured biomass, (b) a generic approach, (c) the thermal‐to‐epithermal neutron ratio ( N r ), and (d) the thermal neutron intensity. Bare soil calibration of the CRNS resulted in high root mean square errors (RMSEs) of 0.097, 0.041, and 0.019 m³/m³ between estimated and reference soil moisture content for sugar beet, winter wheat, and maize, respectively. Considering in‐situ measured biomass for correction reduced the RMSE to 0.015, 0.018, and 0.009 m³/m³. The consideration of thermal neutron intensity for correction was similarly accurate. We also explored the use of CRNS for biomass estimation and found that N r only provided accurate biomass estimates for sugar beet. In contrast, we found significant site‐specific relationships between biomass and thermal neutron intensity for all three crops, suggesting that thermal neutron intensity can be used both to improve CRNS‐based soil moisture content measurements and to quantify crop biomass. Plain Language Summary: Water availability is a key challenge in agriculture, especially given the expected increase of droughts related to climate change. A promising noninvasive technique to monitor soil moisture content is cosmic‐ray neutron sensing (CRNS), which is based on the negative correlation between the number of near‐surface fast neutrons originating from cosmic radiation and the amount of hydrogen stored as soil moisture. However, hydrogen is also stored in other pools, such as biomass. These additional pools of hydrogen must be considered to accurately determine soil moisture content with CRNS. In this study, we used data from three experiments with different crops for comparing four methods for the correction of biomass effects on the measurement of soil moisture content with CRNS. We found that soil moisture content measurements were most accurate when locally measured biomass was considered for correction. We also found that changes in the amount of biomass of different crops can be quantified using thermal neutrons additionally detected by CRNS, that is, neutrons from cosmic rays that have a lower energy than fast neutrons. A correction of biomass effects using thermal neutron measurements also provided accurate soil moisture content measurements. Key Points: Cosmic ray soil moisture measurements were most accurate when corrected with in‐situ biomass measurements or thermal neutron intensity The effect of biomass on epithermal and thermal neutron intensity is plant‐specific Biomass could be estimated from thermal neutron intensity for three crops, but not with the thermal‐to‐epithermal neutron ratio